2012
DOI: 10.1111/j.1439-037x.2012.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Thermal Imaging as a Rapid Tool for Identifying Water‐Stress Tolerant Maize Genotypes of Different Phenology

Abstract: The main task of this research was to evaluate canopy temperature and Crop Water Stress Index (CWSI) by assessing genotype variability of maize performance for different water regimes. To that end, three hundred tropical and subtropical maize hybrids with different phenology in terms of date of anthesis were evaluated. The influence of phenology on the change in canopy temperatures and CWSI was not equal during the three dates of measurement. At the end of vegetative growth (82 days after sowing, DAS) and at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 30 publications
(57 reference statements)
5
86
0
8
Order By: Relevance
“…This is in contrast to the results of Wijayratne et al [17], who showed an increase in canopy temperature with the quantity of dust. The effect of the chemically inert dust on plant physiology is apparently similar to drought stress, which leads to stomatal closure and higher leaf temperature [37]. It is thus important to point out that a possible increase in the plant leaf temperature due to water stress can be excluded in this study, due to the fact that the soil moisture content was always about 70% of the field capacity.…”
Section: Discussionmentioning
confidence: 96%
“…This is in contrast to the results of Wijayratne et al [17], who showed an increase in canopy temperature with the quantity of dust. The effect of the chemically inert dust on plant physiology is apparently similar to drought stress, which leads to stomatal closure and higher leaf temperature [37]. It is thus important to point out that a possible increase in the plant leaf temperature due to water stress can be excluded in this study, due to the fact that the soil moisture content was always about 70% of the field capacity.…”
Section: Discussionmentioning
confidence: 96%
“…DS was imposed by stopping irrigation before flowering to achieve water deficiency at anthesis stage. This treatment induces mild DS, which increases canopy temperature 1°C to 2°C in the absence of HS (Romano et al, 2011;Zia et al, 2013). However, climate conditions varied slightly between the two years of evaluation.…”
Section: Grain Yield Was Affected By Stress Treatmentsmentioning
confidence: 99%
“…It is possible that metabolic pathways are regulated to meet the metabolic demands under each stress condition, resulting in an additive metabolite profile under stress combination unless the metabolic network is collapsed by severe stress treatments. Given that the naturally feasible stresses are imposed more mildly than typical stress treatments in greenhouse experiments (Romano et al, 2011;Zia et al, 2013), the general metabolic response in stress combination should be considered as the sum of individual stresses in the field. This is also supported by PCA, in which drought and heat contribute the majority of the variance observed in the metabolic data, with principal component 1 separating DS from the WW condition, principal component 2 separating HS from no HS, and DS+HS being separated from the WW condition in an additive fashion.…”
Section: Effects Of Ds+hsmentioning
confidence: 99%
“…In rainfed environments, elevated temperatures will increase the evapotranspirative demand from the atmosphere, negatively affecting crop water balance and thus inducing drought stress. In water-limited conditions plants partially close their stomata to reduce water loss through transpiration, resulting in the leaves becoming warmer (Jackson et al 1981) and canopy temperature can rise by over 9°C (Garrity and O'Toole 1995;Zia et al 2013). Atmospheric CO 2 is expected to double by the end of this century (Meehl et al 2007).…”
Section: Reducing the Effects Of Climate Change On Farmers In Maize-bmentioning
confidence: 99%